A Performance Analysis of System Rollback Techniques - Sousa, Antônio Drumond Cota de; Freitas, Henrique Cota de (Anais Estendidos do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2025: Anais Estendidos do XXVI Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/sscad_estendido.2025.15828, 2025)
System restorations are crucial for maintaining operational continuity, yet the lack of comparative performance data makes selecting the right rollback tool a significant challenge. This paper addresses this gap by conducting a quantitative performance analysis of four popular techniques: NixOS Generations, Snapper, Timeshift (in RSYNC mode), and Windows System Restore. We evaluated each tool based on two key metrics: rollback duration and snapshot storage size, using a controlled virtualized environment. Our results reveal significant performance disparities, with rollback speeds differing by up to a factor of four, indicating that filesystem-integrated, copy-on-write tools are demonstrably more efficient for performance-critical applications.